Evaluation of an early weaning program for dairy calves - J.L. Morrill; M.K. Schmidt; A.J. Cullen; M.B. Morrill (Kansas Agricultural Experiment Station Research Reports, 1984)
One experiment was conducted to compare an early weaning program, using a prestarter , when calves were weaned at 2 or 3 wk of age with programs using conventional feeds and weaning at 3 or 6 wk of age. Daily gains to 8 wk of age were 1.19 and 1.03 pound for calves fed a commercial starter and weaned at 6 and 3 weeks of age, respectively; and were 1.1 and .97 for calves on the early weaning program and weaned at 3 and 2 wk of age, respectively. Another experiment was conducted to test one variation of the early weaning program. Calves fed according to the early weaning program and receiving a high quality, fibrous starter gained an average of 1.3 lb per day to 6 wk of age. Calves fed prestarter but no starter until weaning did not perform as well.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Weaning; Feed consumption; Weight gain